Targeting KRAS: The Elephant in the Room of Epithelial Cancers - Merz, Valeria; Gaule, Marina; Zecchetto, Camilla; Cavaliere, Alessandro; Casalino, Simona; Pesoni, Camilla; Contarelli, Serena; Sabbadini, Fabio; Bertolini, Monica; Mangiameli, Domenico; Milella, Michele; Fedele, Vita; et al. (Frontiers in Oncology, 2021)
Mutations of the proto-oncogene KRAS are the most frequent gain-of-function alterations found in cancer. KRAS is mutated in about 30% of all human tumors, but it could reach more than 90% in certain cancer types such as pancreatic adenocarcinoma. Although historically considered to be undruggable, a particular KRAS mutation, the G12C variant, has recently emerged as an actionable alteration especially in non-small cell lung cancer (NSCLC). KRASG12C and pan-KRAS inhibitors are being tested in clinical trials and have recently shown promising activity. Due to the difficulties in direct targeting of KRAS, other approaches are being explored. The inhibition of target upstream activators or downstream effectors of KRAS pathway has shown to be moderately effective given the evidence of emerging mechanisms of resistance. Various synthetic lethal partners of KRAS have recently been identified and the inhibition of some of those might prove to be successful in the future. The study of escape mechanisms to KRAS inhibition could support the utility of combination strategies in overcoming intrinsic and adaptive resistance and enhancing the clinical benefit of KRASG12C inhibitors. Considering the role of the tumor microenvironment in influencing initiation and promotion, the immune tumor niche of KRAS mutant tumors has been deeply explored and characterized for its unique immunosuppressive skewing. However, a number of aspects remain to be fully understood, and modulating this tumor niche might revert the immunoresistance of KRAS mutant tumors. Synergistic associations of KRASG12C and immune checkpoint inhibitors are being tested.